USE OF FOLK REMEDIES AMONG PATIENTS IN KARACHI PAKISTAN - Qidwai, Waris; Alim, Salman Raza; Dhanani, Raheem H; Jehangir, Sana; Nasrullah, Aysha; Raza, Ammara (Journal of Ayub Medical College Abbottabad, 2003)
Background: The concept that food is medicine is being practiced in certain parts of the world, with positive outcomes on health of the population. We have such practice in Pakistan but it needs to be brought in line with the available scientific evidence. Methods: The study was conducted on 270 patients, visiting the Family Practice Center, the Aga Khan University, Karachi. A questionnaire was used to collect information on the demographic profile, and the use of folk remedies for medicinal uses. Results: Substantial use of folk remedies for different medical conditions has been documented. The remedies included cinnamon, ginger, cloves, cordimon, sesame oil, poppy seeds, honey, lemon, table salt, eggs and curd. The medical conditions in which folk remedies are used in respondents' view, include conditions such as common cold, cough and flu to more serious conditions such as asthma, jaundice and heat stroke. Conclusions: We have found a substantial use of folk remedies for treatment of medical conditions. There is a need to organize their use on scientific lines. Key-words: Traditional medicine; Folk remedies; Primitive medicine